Sports nutrition: Current and novel insights - Nieman, D. C. (Nutrients, 2025)
This Special Issue invited the submission of sports nutrition-based manuscripts that advanced scientific understanding and provided novel insights on all aspects of performance and recovery. Exercise performance and recovery can be enhanced through prudent training- and nutrition-based approaches. The early history of sports nutrition was based on the importance of increased intake of carbohydrates and adequate hydration. Sports nutrition has entered a new era of investigation due to advances in technology, research designs, and data computational methods. In multi-omics studies, investigators utilize technologies from genomics, transcriptomics, proteomics, metabolomics, and epigenomics to gain a comprehensive understanding of biological systems. Human system biology approaches based on multi-omics outcomes have revealed significant influences of a wide variety of specific foods and supplements on physiological responses to exercise that were previously ignored [1,2]. As emphasized by Bedrac et al. in a scoping review [1], the number of multi-omics-based sports nutrition studies is expanding, but most are focused on discovering novel biomarkers. There is little evidence that these are linked significantly to athletic endeavors and long-term health. Multi-omics outcomes are a key component of precision sports nutrition that seeks to optimize nutrition guidelines at the individual athlete level for long-term performance and health. However, precision sports nutrition is currently considered an emerging science that will require continued advancement before it becomes practical and advantageous at the individual athlete level [2].